2017
DOI: 10.1148/radiol.2016160572
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Hepatic Arterial Infusion Chemotherapy with Oxaliplatin and 5-Fluorouracil for Advanced Perihilar Cholangiocarcinoma

Abstract: Purpose To evaluate the efficacy and safety of hepatic arterial infusion (HAI) of oxaliplatin and 5-fluorouracil for advanced perihilar cholangiocarcinoma (PCC) in this prospective phase II study. Materials and Methods The protocol was approved by the local ethics committee, and all patients gave informed consent. Patients with nonresectable PCC were included in a prospective, open phase II study investigating HAI through interventionally implanted port catheters. HAI consisted of infusions of oxaliplatin 40 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 45 publications
0
54
0
1
Order By: Relevance
“…Moreover, our study showed that patients with high PLR had more frequent liver recurrences and recurrences within 1 year of surgery than did patients with low PLR. These results suggest that surgeons might want to administer adjuvant chemotherapy or hepatic arterial infusion chemotherapy to patients with high PLR values (34,35).…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, our study showed that patients with high PLR had more frequent liver recurrences and recurrences within 1 year of surgery than did patients with low PLR. These results suggest that surgeons might want to administer adjuvant chemotherapy or hepatic arterial infusion chemotherapy to patients with high PLR values (34,35).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, some important clinicopathological parameters and widely used tumor biomarkers for pCCA, such as surgical margin status, the information of serum carbohydrate antigen 19 − 9 (CA199), carcinoembryonic antigen (CEA) and vascular encasement were unavailable in SEER database. In addition, many promising options like interventional therapy [49], immunotherapy [50] and targeted treatment [51] are enjoying increasing popularities among pCCA patients, but it is a pity that they have been inaccessible in SEER program until now. As a user-friendly method for prognosis prediction and decision-making, there is di culty in providing everlastingly excellent prognosis prediction in clinical practice, because not all signi cant prognostic factors were embodied in this tool.…”
Section: Discussionmentioning
confidence: 99%
“…Selected studies of the 3 strategies are summarized in Table 3, focusing on prospective or comparative studies when available. [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119] The analysis is a difficult one because very few studies are prospective or comparative, while most have a low number of patients and describe single-centre experience. Moreover, there is a high heterogeneity in terms of patient population within and across studies that limits the interpretability of data.…”
Section: Selective Internal Radiation Therapymentioning
confidence: 99%